Effects of Gelatin Hydrogel Containing Anti-Transforming Growth Factor-β Antibody in a Canine Filtration Surgery Model - Maeda, Michiko (Int J Mol Sci, 2017)
In this present study, we investigated the effect of a controlled release of anti-transforming growth factor β (TGF-β) antibody on intraocular pressure (IOP), bleb formation, and conjunctival scarring in a canine glaucoma filtration surgery model using gelatin hydrogel (GH). Glaucoma surgery models were made in 14 eyes of 14 beagles and divided into the following two groups: (1) subconjunctival implantation of anti-TGF-β antibody-loaded GH (GH-TGF-β group, n = 7), and (2) subconjunctival implantation of GH alone (GH group, n = 7). IOP and bleb features were then assessed in each eye at 2- and 4-weeks postoperative, followed by histological evaluation. We found that IOP was significantly reduced at 4-weeks postoperative in the two groups (p < 0.05) and that IOP in the GH-TGF-β-group eyes was significantly lower than that in the GH-group eyes (p = 0.006). In addition, the bleb score at 4-weeks postoperative was significantly higher in the GH-TGF-β group than in the GH group (p < 0.05), and the densities of fibroblasts, proliferative-cell nuclear antigen (PCNA)-positive cells, mast cells, and TGF-β-positive cells were significantly lower in the GH-TGF-β group than in the GH group. The findings of this study suggest that, compared with the GH-group eyes, implantation of anti-TGF-β antibody-loaded GH maintains IOP reduction and bleb formation by suppressing conjunctival scarring due to the proliferation of fibroblasts for a longer time period via a sustained release of anti-TGF-β antibody from GH.